2017
DOI: 10.1080/17435390.2017.1287313
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytotoxic and inflammatory potency of amorphous silicon dioxide nanoparticles of similar size in multiple cell lines

Abstract: The likelihood of environmental and health impacts of silicon dioxide nanoparticles (SiNPs) has risen, due to their increased use in products and applications. The biological potency of a set of similarly-sized amorphous SiNPs was investigated in a variety of cells to examine the influence of physico-chemical and biological factors on their toxicity. Cellular LDH and ATP, BrdU incorporation, resazurin reduction and cytokine release were measured in human epithelial A549, human THP-1 and mouse J774A.1 macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 62 publications
5
48
0
Order By: Relevance
“…Furthermore, Rabolli and coworkers , examining 17 monodisperse non‐crystalline silica particles in different cell types, concluded that the in vitro cytotoxic activity is governed by a complex interplay of their physicochemical parameters, including the surface area; however, this varied markedly with the cell types. Recently, Breznan and coworkers found that particle surface acidity seemed to be the most significant determinant for the overall biological activity of SiNPs. In extension of this, our previous study showed that the choice of exposure medium could be crucial for the cytokine responses obtained upon exposure to silica particles of different sizes and that this is important for interpreting results reported from in vitro studies of NPs and other particulates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rabolli and coworkers , examining 17 monodisperse non‐crystalline silica particles in different cell types, concluded that the in vitro cytotoxic activity is governed by a complex interplay of their physicochemical parameters, including the surface area; however, this varied markedly with the cell types. Recently, Breznan and coworkers found that particle surface acidity seemed to be the most significant determinant for the overall biological activity of SiNPs. In extension of this, our previous study showed that the choice of exposure medium could be crucial for the cytokine responses obtained upon exposure to silica particles of different sizes and that this is important for interpreting results reported from in vitro studies of NPs and other particulates.…”
Section: Discussionmentioning
confidence: 99%
“…The particles were assumed as spherical and the diameters of the sphere fitting the individual particles were recorded as their size. The elemental analysis of the above particles was carried out using inductively coupled plasma–MS method reported elsewhere (Breznan et al, ). Particle size and the agglomeration state in liquid (ultrapure water and DMEM +5% FBS media) were determined by dynamic light scattering (DLS), while the surface charge of the particle suspensions was assessed based on the electrokinetic (zeta) potential of the particles (Das et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These assays allow for rapid, high‐throughput assessment of PM impacts on cell viability, metabolism and function in a cost‐effective manner. We have previously developed a high‐throughput method for similar cytotoxicity evaluation of PM and nanoparticles (Breznan et al, ; Breznan et al, ; Kumarathasan et al, ; Thomson et al, ), which allows to rapidly screen particles based on the viability of these cells. However, most significant changes due to particle exposures are observed with relatively higher doses of PM exposures, and these assays are limited in terms of providing detailed mechanistic information.…”
Section: Introductionmentioning
confidence: 99%
“…Drug stability and the duration of intracellular drug accumulation by nanoparticle uptake are correlated with cytotoxicity A549 (25). It is known that the free form of the drug diffuses across the cell membrane when used as a solution.…”
Section: In Vitro Cytotoxicity Of Cur-nlcmentioning
confidence: 99%
“…It is known that the free form of the drug diffuses across the cell membrane when used as a solution. Therefore, further entry will be rapidly confined when reaching saturation inside the protoplasm, which showed weak cytotoxicity for a very short time (25,26). however, Cur-NLC as a nanocarrier had abundant availability inside the cell by endocytosis and encapsulated curcumin exerted sustained cytotoxicity.…”
Section: In Vitro Cytotoxicity Of Cur-nlcmentioning
confidence: 99%